2020
DOI: 10.3390/nu12071923
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Composition and Nutritional Status with Functional Recovery in Stroke Rehabilitation Patients

Abstract: Previous studies have suggested that the nutritional status after stroke is independently associated with long-term outcomes and that sarcopenia delays poststroke rehabilitation and worsens the prognosis. However, many stroke patients have a deteriorated nutritional status and a decreased muscle mass in the acute phase. This prospective study included 179 patients who were admitted to the stroke rehabilitation unit. We performed bioelectrical impedance analysis and determined the Geriatric Nutritional Risk Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 36 publications
0
59
0
1
Order By: Relevance
“…Many studies have shown that physical exercise has a great impact on human body mechanisms and functions. Excessive high-load exercise training can damage human body functions, but proper physical exercise can effectively improve the patient's body mechanisms [22,23]. rough exercise, patients with dyslipidemia can change their body shape and composition, reduce fat and sugar in the body, achieve fitness goals, and at the same time help their recovery.…”
Section: Exercise Methods For Patients With Dyslipidemiamentioning
confidence: 99%
“…Many studies have shown that physical exercise has a great impact on human body mechanisms and functions. Excessive high-load exercise training can damage human body functions, but proper physical exercise can effectively improve the patient's body mechanisms [22,23]. rough exercise, patients with dyslipidemia can change their body shape and composition, reduce fat and sugar in the body, achieve fitness goals, and at the same time help their recovery.…”
Section: Exercise Methods For Patients With Dyslipidemiamentioning
confidence: 99%
“…Current post-stroke rehabilitation interventions treat muscle function (mainly motor function) and cognitive function separately. Irisawa et al’s prospective study included 179 patients recruited from two stroke rehabilitation units in Japan [ 58 ]. Lean mass was assessed by BIA and nutrition status using the Geriatric Nutritional Risk Index.…”
Section: What Interventions Exist For Post-stroke Rehabilitation mentioning
confidence: 99%
“…In BIA, phase angle is an important parameter, which is composed of tissue resistance and reactance, and represents muscle cellular integrity. Irisawa et al have reported that a high phase angle is associated with a motor score of the Functional Independence Measure at four weeks (OR, 3.32) in patients with stroke [69].…”
Section: Applications In Strokementioning
confidence: 99%